If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t(2t + -7) = 0 Reorder the terms: 3t(-7 + 2t) = 0 (-7 * 3t + 2t * 3t) = 0 (-21t + 6t2) = 0 Solving -21t + 6t2 = 0 Solving for variable 't'. Factor out the Greatest Common Factor (GCF), '3t'. 3t(-7 + 2t) = 0 Ignore the factor 3.Subproblem 1
Set the factor 't' equal to zero and attempt to solve: Simplifying t = 0 Solving t = 0 Move all terms containing t to the left, all other terms to the right. Simplifying t = 0Subproblem 2
Set the factor '(-7 + 2t)' equal to zero and attempt to solve: Simplifying -7 + 2t = 0 Solving -7 + 2t = 0 Move all terms containing t to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 2t = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 2t = 0 + 7 2t = 0 + 7 Combine like terms: 0 + 7 = 7 2t = 7 Divide each side by '2'. t = 3.5 Simplifying t = 3.5Solution
t = {0, 3.5}
| 85=15x^2 | | 18-2(x+3)= | | (8+4)*5+10-18+7+5*(7+1*4)+6= | | 4x-4x(4x-4x)= | | 4x^2-1=8x | | 7x-97=4x-13 | | 211-4x=32x+19 | | logy=1.6 | | 2x+x+400+2x=5000 | | x(x-20)=525 | | 75-2x=2x+19 | | -16-2x=-10x | | 3(x-2)-5(3-4x)=29-2x | | p^2-20-8p=0 | | (-2.6)+7=7+(-2.6) | | 20+8p=p^2 | | 9b+36=b^2 | | 6-(-15)= | | 3x=15y | | (-3y^2)(2xy)(-x)= | | 16X^3-24x^2-12x-14=0 | | (-3y^2)(2xy)= | | 2*(2+2)/2= | | 8x^2=7x | | f^2=10f-16 | | a^2+8a-9=0 | | (c-6)(c-3)=23 | | 5w*u*u= | | x(x-1)=x | | a(a-5)= | | 7x-14=48-14x-28 | | 2x+4=36-2x |